Brogdon's forensic radiology - Thali, Michael J.; Viner, Mark D.; Brogdon, B. G. (Byron Gilliam). (Boca Raton, FL : CRC Press, 2011)
'Brogdon's Forensic Radiology demonstrates the application of radiology in cases involving identifying remains, evaluating causes of death, and establishing evidence. This second edition features new material on the large scale investigation of war crimes and human rights abuses; recent technological changes and the role of virtual autopsies; the use of sectional imaging for dental identification; reconstruction of gunshot injuries; new techniques for portable x-ray, computerized data recording, and image analysis post-processing; as well as increased coverage of applications in non-biological materials. Case studies feature tsunamis and the London bombings'-- Provided by publisher.
Rev. ed. of : Forensic radiology / B.G. Brogdon, 1998.
Keywords: Forensic radiography; Medical jurisprudence